Associations of HLA alleles with specific language impairment. - Nudel, R; Simpson, N; Baird, G; O'Hare, A; Conti-Ramsden, G; Bolton, P; Hennessy, E; Monaco, A; Knight, J; Winney, B; Fisher, SE; Newbury, D (Springer New York LLC, 2014)
BACKGROUND: Human leukocyte antigen (HLA) loci have been implicated in several neurodevelopmental disorders in which language is affected. However, to date, no studies have investigated the possible involvement of HLA loci in specific language impairment (SLI), a disorder that is defined primarily upon unexpected language impairment. We report association analyses of single-nucleotide polymorphisms (SNPs) and HLA types in a cohort of individuals affected by language impairment. METHODS: We perform quantitative association analyses of three linguistic measures and case-control association analyses using both SNP data and imputed HLA types. RESULTS: Quantitative association analyses of imputed HLA types suggested a role for the HLA-A locus in susceptibility to SLI. HLA-A A1 was associated with a measure of short-term memory (P = 0.004) and A3 with expressive language ability (P = 0.006). Parent-of-origin effects were found between HLA-B B8 and HLA-DQA1*0501 and receptive language. These alleles have a negative correlation with receptive language ability when inherited from the mother (P = 0.021, P = 0.034, respectively) but are positively correlated with the same trait when paternally inherited (P = 0.013, P = 0.029, respectively). Finally, case control analyses using imputed HLA types indicated that the DR10 allele of HLA-DRB1 was more frequent in individuals with SLI than population controls (P = 0.004, relative risk = 2.575), as has been reported for individuals with attention deficit hyperactivity disorder (ADHD). CONCLUSION: These preliminary data provide an intriguing link to those described by previous studies of other neurodevelopmental disorders and suggest a possible role for HLA loci in language disorders.